Hydroxychloroquine in COVID-19 patients: what still needs to be known about the kinetics - Martin-Blondel, G (Clin Infect Dis, 2020)
Different dosage regimens of hydroxychloroquine are used to manage COVID-19 patients, without information on the pharmacokinetics in this population.Blood samples (n=101) were collected from 57 COVID-19 patients for 7 days and concentrations were compared with simulated kinetic profiles.Hydroxychloroquine exposure is low and cannot be predicted by other populations.